2019
DOI: 10.1021/acs.jmedchem.9b00162
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Mapping of Isoform-Selectivity Determinants for J-Channel-Binding Inhibitors of Sphingosine Kinases 1 and 2

Abstract: Sphingosine kinase enzymes (SK1 and SK2) catalyse the conversion of sphingosine into sphingosine 1-phosphate and play a key role in lipid signaling and cellular responses. Mapping of isoform amino acid sequence differences for SK2 onto the recently available crystal structures of SK1 suggests that subtle structural differences exist in the foot of the lipid-binding 'J-channel' in SK2, the structure of which has yet to be defined by structural biology techniques. We have probed these isoform differences with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…In this regard, mapping SK2 amino acid differences onto the SK1 crystal structure indicates subtle differences in the ‘foot’ of ‘J‐channel’ (which accommodates sphingosine) of the two isoforms. Probing these isoform‐specific differences with a chemical series (derived from the potent SK1‐selective inhibitor, PF‐543) demonstrated that it was possible to systematically turn a 100‐fold SK1‐selective inhibitor, through chemical modification, to an equipotent SK1/SK2 inhibitor (Compound 49, pIC 50 7.8) and, with further modification, to a 100‐fold SK2 selective inhibitor, with nanomolar potency (HWG‐35D (Compound 55), pIC 50 7.4) [132]. In addition, structure–activity relationship profiling has identified a side cavity in SK2 that can be exploited to increase inhibitor potency, with relatively small hydrophobic moieties preferred (e.g., SLM6071469, K i = 89 n m , 73‐fold SK2 selective) [133].…”
Section: Sk Inhibitor Developmentmentioning
confidence: 99%
“…In this regard, mapping SK2 amino acid differences onto the SK1 crystal structure indicates subtle differences in the ‘foot’ of ‘J‐channel’ (which accommodates sphingosine) of the two isoforms. Probing these isoform‐specific differences with a chemical series (derived from the potent SK1‐selective inhibitor, PF‐543) demonstrated that it was possible to systematically turn a 100‐fold SK1‐selective inhibitor, through chemical modification, to an equipotent SK1/SK2 inhibitor (Compound 49, pIC 50 7.8) and, with further modification, to a 100‐fold SK2 selective inhibitor, with nanomolar potency (HWG‐35D (Compound 55), pIC 50 7.4) [132]. In addition, structure–activity relationship profiling has identified a side cavity in SK2 that can be exploited to increase inhibitor potency, with relatively small hydrophobic moieties preferred (e.g., SLM6071469, K i = 89 n m , 73‐fold SK2 selective) [133].…”
Section: Sk Inhibitor Developmentmentioning
confidence: 99%
“…The SK2 inhibitor, ABC294640 has been reported to induce the ubiquitin-proteasomal degradation of SK1 and DES1 [16,17]. In contrast, another SK2 inhibitor, (R)-FTY720 methyl ether (ROMe), does not induce the proteasomal degradation of SK1 [25].…”
Section: Neither Sk1 Nor Des1 Protein Levels Were Altered By a Novel Selective Sk2 Inhibitor Hwg-35dmentioning
confidence: 99%
“…Sci. 2020, 21, x FOR PEER REVIEW 3 of 16 the efficacy of SK2 inhibition in IMQ-induced psoriasis mouse models using a novel specific SK2 inhibitor, HWG-35D [17].…”
Section: Neither Sk1 Nor Des1 Protein Levels Were Altered By a Novel Selective Sk2 Inhibitor Hwg-35dmentioning
confidence: 99%
See 2 more Smart Citations